Strategies for Enhancing Training and Development in Healthcare Management - Willie, Michael Mncedisi (Advances in Human Resource Management Research, 2025)
Purpose: This study examines strategies to enhance training and development in healthcare management, particularly in response to challenges posed by the COVID-19 pandemic. It aims to identify and assess training needs, emphasizing customized approaches to address emerging demands. Research Design and Methodology: This study employed a qualitative approach incorporating a literature review and case studies. The study focused on the pandemic’s impact on healthcare management strategies and evaluated key training requirements. Findings and Discussion: The research identified critical training needs, including health record management, supply chain processes, patient-centered care, customer service, financial management, corporate governance, and fostering a learning organization. Implications: The findings highlight the importance of tailored training programs to improve operational efficiency, patient care, financial stability, and continuous learning. This study offers valuable insights for healthcare organizations to adapt and thrive in a post-COVID-19 landscape.